Language and interpretation in the Syriac text of Ben Sira : a comparative linguistic and literary study - Peursen, W. Th. van. (Monographs of the Peshiṭta Institute, Leiden. Studies in the Syriac versions of the Bible and their cultural contexts ;, 2007)
This book is the result of an innovative linguistic study of the Syriac translation of Ben Sira. It contains both a traditional philological analysis, incorporating matters of text-historical interest and translation technique, and also the results of a computational linguistic analysis of phrases, clauses and texts. It arrives at new linguistic insights, including a proposal for a corpus-based description of phrase structure based on a so-called maximum matrix. The book also addresses the fundamentally different way in which a text is approached in a computer-assisted analysis compared with the way in which this is done in traditional philological approaches. It demonstrates how the computer-assisted analysis can fruitfully shed light on or supplement traditional philological research.